Tratamento intensivo baseado na Terapia de Aceitação e Compromisso para dificuldades relacionadas ao peso - Freitas, Breno Irigoyen de (2016)
This study evaluated the effect of an Acceptance and Commitment Therapy (ACT) intervention on experiential avoidance, Body Mass Index (BMI) and weight related difficulties. Overweight and obesity rates have risen in recent decades in Brazil and worldwide, and are associated with considerable health impairments. Some weight-loss treatments have demonstrated short-term effectiveness, however, about 80% of people recover weight in a few years. The experiential avoidance, low experiential awareness, and lack of motivation have been identified as key elements which are not sufficiently addressed in weight reduction programs. This study has a quantitative and pre-experimental design. Inclusion criteria: female, aged between 18 and 59 years, IMC≥25Kg/m² and eight years of minimum education. Exclusion criteria: Major Depressive Episode, Manic or Hypomanic, Borderline Personality Disorder and Substance Use Disorder. The instruments used were: Acceptance and Action Questionnaire (AAQ-II), Acceptance and Action Questionnaire for Weight (AAQ-W), Cognitive Fusion Questionnaire (CFQ), Diet and Exercise Scale (DES), Body Shape Questionnaire ( BSQ), Mindful Eating Questionnaire (MEQ) and Valued Living Questionnaire (VLQ), and BMI. The first section aimed to evaluate the effect of an ACT intervention on: BMI, experiential avoidance, dissatisfaction with body image, mindful eating, and behaviors related to diet and physical activity. Section II evaluated the difference of the intervention effects for women with different levels of symptoms of binge eating. The 59 participants had a mean age 44.7 years (SD = 11.1) and average 14.7 years of formal education (SD = 3.4). At follow-up, 17% of participants showed weight reduction, maintenance 79.2% and 1.9% weight gain. The experiential avoidance related to weight reduced over time. The results indicate greater sensitivity of the AAQ-W compared to the AAQ-II for the population studied. There was a reduction of 48.04% in the frequency of binge eating and 30.99% in choosing unhealthy meals. Binge eating showed a positive correlation with experiential avoidance, dissatisfaction with body image, and compulsive eating, beyond negative correlation with mindful eating. Moderate and severe symptoms groups showed significant reductions in experiential avoidance and body image dissatisfaction at follow up. Severe symptoms group showed stronger effect size compared to others and significant increase in physical activity. The results show an increase in mindful eating regardless of the level of binge eating. The results showed that the intervention led to reductions in experiential avoidance and body image dissatisfaction, especially among women with severe binge eating symptoms. This difference can be explained by the role of experiential avoidance in maintaining of compulsive eating. Among the limitations of this study are the high dropout rate and the absence of a standard instrument for measuring binge eating over time.